Effects of Mg substitution at Sr site on superconductivity of Tl0.5Pb0.5Sr2-xMgxCa0.8Yb0.2 O7-δ (x=0.0-1.0) ceramics / Suhadir Shamsuddin. - Shamsuddin, Suhadir (2009)
In this project, Mg substituted T11212 type phase high temperature superconductor with nominal starting compositions of Tl0.5Pb0.5Sr2-xMgxCa0.8Yb0.2O7-δ (x=0.0-1.0) were synthesized using conventional solid-state synthesis method. Power X-ray diffraction (XRD) patterns showed all samples consist of major 1212 phase and minor 1201 phase. Temperature-dependent resistance measurement on (x=0.0) showed metallic normal state behavior. Substitution of Mg caused deterioration of superconductivity and gradual change of normal state resistance from semi-metallic behavior (x=0.2-0.8) to semiconductor-like behavior (x=1.0). The (x=1.0) sample was non-superconducting. The best superconducting behavior of the series was observed for Tl0.5Pb0.5Sr2Ca0.8Yb0.2Cu2O7 with Tc zero and Tc onset, are 92K and 103K respectively. Results of critical temperature (Tc) measurements, microstructure investigation using scanning electron microscope (SEM) and power X-ray diffraction (XRD) analysis are presented. The effects of Mg substitution are discussed in terms of lattice parameter which is decrease on both a-lattice and c-lattice parameter and the concepts of an average Cu valence as well as the changing in normal state behavior.